Analisis Tingkat Kerusakan Dan Estimasi Biaya Pemeliharaan Bangunan Gedung Rusunawa Putri Universitas Jember - Pramudya Restuning Kawedar, Hening; Trisiana, Anita; Arifin, Syamsul (Journal of Applied Civil Engineering and Infrastructure Technology, 2022)
Damage to buildings makes the building less comfortable to live in, so identification of damage is needed and how efforts to deal with it and the cost of repairs. This research was conducted by taking an object in the building Rusunawa Putri University of Jember by conducting a direct survey. The data obtained is then analyzed to determine the type of damage to buildings that occur and the repair and repair costs. From the results of this study note that in the Rusunawa Putri University of Jember building identified 7 (nine) types of damage, namely: weathering of the ceiling (ceiling), lights off, cracked and moist walls, window supports, window hinges, door frames, and doors door lock release. The index value of the condition of the Putri Rusunawa building is 99.59% so it is included in the condition index in zone 1 between 85% -100% which has excellent conditions. The analytical method used to determine the cause of damage is the Fishbone Diagram. From the results of the analysis of the dominant causes of damage namely by human factors, management factors, and material factors. The suggested remedial action is a routine check from the manager. The cost of building repairs is Rp 89.855.416